Business and government interdependence in emerging economies: Insights from hotels in Ghana. (12th September 2017) - Amankwah‐Amoah, Joseph; Debrah, Yaw A.; Honyenuga, Ben Q.; Adzoyi, Paulina N.
Abstract: Although social science research is replete with scholarly works on capacity building, relatively few studies have focused on how government can induce capacity building among privately owned enterprises in emerging economies. We seek to fill the lacuna in our understanding by examining how a government can induce capacity building among privately owned enterprises. The study adopted a qualitative approach using semi‐structured interviews with hotel owners, employees, and managers, as well as government officials in Ghana to examine the issue. We identified three unique stages through which such capacity‐building initiatives unfold encompassing diagnosing, renewal, and customer centricity. The study revealed that capacity building through collaborative partnership was partly motivated by desire to overcome societal resistance to services seen as "tainted." The concluding section outlines a number of theoretical and practical implications.